CYBERBULLYING IN THE DIGITAL ERA AMONG ADOLESCENTS: A DESCRIPTIVE LITERATURE REVIEW - Putri Desi Adryanti Subu Taopan (CV. TOTUS TUUS, 2026)
The increasing intensity of adolescent social media use has been followed by a growing risk of cyberbullying, a form of online aggression that can disrupt psychological well-being, social interaction, and academic functioning. This study aimed to examine the forms, contributing factors, impacts, and prevention strategies of cyberbullying among adolescents through a descriptive literature review. The study analyzed 15 national and international scientific articles published between 2015 and 2025. The articles were identified through Google Scholar, Semantic Scholar, ScienceDirect, and Garuda using the keywords “cyberbullying,” “adolescents,” and “social media.” The selection process applied inclusion criteria related to topic relevance, focus on adolescent populations, publication period, and full-text availability. The selected studies were analyzed through content analysis and thematic synthesis, including data reduction, coding, categorization, and interpretation of recurring patterns. The review shows that the most frequent forms of cyberbullying include online insults, body shaming, impersonation, social exclusion, and the dissemination of embarrassing content. The dominant contributing factors are anonymity, low digital literacy, peer pressure, oversharing behavior, and limited parental supervision. The major impacts include anxiety, depression, reduced self-esteem, social withdrawal, and decreased academic performance. The findings indicate that cyberbullying prevention requires integrated digital literacy education, family supervision, school-based counseling support, and policy-level protection. This literature-based synthesis contributes to a more coherent understanding of cyberbullying among adolescents and highlights the importance of collaborative prevention efforts in the digital era.